THE INFLUENCE OF DIGITAL MARKETING, PRODUCT QUALITY AND PRICE PERCEPTION ON PURCHASE DECISION AT THE RURI CONVECTION HOUSE INDUSTRY IN PUNTEUT LHOKSEUMAWE CITY - Azmiatun; Nurainun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examined the effect of digital marketing, product quality, and price on purchase decisions in the Ruri convection home industry in Punteut, Lhokseumawe City. This study used primary data obtained by distributing questionnaires to 108 respondents selected using the purposive sampling method. The data analysis methods used were multiple linear regression and simple regression methods with the help of SPSS. The results of the study partially showed that digital marketing had a positive and significant effect on purchase decisions at the Ruri convection home industry in Punteut, Lhokseumawe City, product quality had a positive and significant effect on purchase decisions at the Ruri home convection industry in Punteut, Lhokseumawe City, and the price had a positive and significant effect on purchase decisions in the Ruri convection home industry in Punteut, Lhokseumawe City. Simultaneously, digital marketing, product quality, and price had a positive and significant effect on purchase decisions at the Ruri convection home industry in Punteut, Lhokseumawe City.